KUALITAS LAYANAN PERGURUAN TINGGI YANG BERPENGARUH TERHADAP KEPUASAN MAHASISWA DAN KONSEKUENSI PERILAKU MAHASISWA - Imam nuraryo (Jurnal Ekonomi Perusahaan, 2016)
The purpose of this paper is to  analyze  the  influence  of  perceived  service  quality,  perceived  value, image  on student satisfaction, and determine the consequences of student satisfaction in  one private Bandung University (Prima University). In order to accomplish the  objectives proposed, a  model reflecting the  influence of perceived service quality, perceived value, image on student satisfaction, and reflecting the relationship bet ween satisfaction and behavioral consequences, the model is tested by structural equations and the final sample is 280 students. The findings show that image has a positive effect on student satisfaction, and  the  satisfaction has a  positive  effect  on  student  loyalty ,and  negative  effect  on  student complaint, if higher education institutions have  to compete through student  satisfaction, It  is proven by  this paper  that  the  construct  which  most  influences student  satisfaction in  higher education is the image construct ,also it is proven that if  the student satisfaction rises, the loyalty will increase and complaint will decrease.